Relationship Between Body Mass Index, Blood Sugar, Cholesterol, and Uric Acid Levels in Infertile Women - Amansyah, Adek; Wilim, Cindy; Meldawati, Meldawati (Journal of Neonatal Surgery, 2025)
Background: Fertility issues are very important for married couples. Not all married couples have children easily due to infertility. This study aims to determine the relationship between body mass index, blood sugar, cholesterol, and uric acid levels in infertile women. Method: This type of research is quantitative analytical with a cross-sectional approach. This research was conducted at Royal Prima Medan Hospital in March-April 2024. The study population was women aged 21-40 years and accompanied by an obese body mass index >30, blood sugar, cholesterol, and uric acid levels. The sample size was 30 people using purposive sampling. Data analysis was done univariate, bivariate with chi-square, and multivariate with multiple logistic regression. Results: Based on the results of the study, it can be stated that there is a significant relationship between blood sugar levels (p=0.030) and cholesterol (p=0.000) with body mass index, while uric acid was not found to have a significant relationship with body mass index (p=0.103) in infertile women at Royal Prima Hospital. There is no relationship between body mass index and infertility (p=0.103) in women at Royal Prima Hospital. Conclusion: Thus, this study concludes that women who have uncontrolled blood sugar levels and abnormal cholesterol can cause infertility. It is recommended that married couples who have not had children should consult a doctor to find out solutions that can be done to overcome infertility problems, as well as maintain a body mass index in the normal category, a healthy lifestyle, and routine health control to prevent an increase in blood sugar, cholesterol and uric acid levels